2015
DOI: 10.7189/jogh.05.020411
|View full text |Cite
|
Sign up to set email alerts
|

Birth prevalence of selected external structural birth defects at four hospitals in Dar es Salaam, Tanzania, 2011–2012

Abstract: Background94% of all birth defects (BD) and 95% of deaths due to the BD occur in low and middle income countries, many of which are preventable. In Tanzania, there is currently a paucity of BD data necessary to develop data informed prevention activities.MethodsA cross-sectional analysis was conducted of deliveries identified with BD in the labor ward registers at four Dar es Salaam hospitals between October, 2011 and February, 2012. The birth prevalence of structural BD, case fatality proportion, and the dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 18 publications
1
26
0
Order By: Relevance
“…In Africa, neonatal and perinatal deaths due to congenital abnormalities are much higher compared to Europe. In Tanzania, a high perinatal death of 66.7% and neonatal death of 18.5% are caused by congenital malformations . In Nigeria, an earlier study reported about 16% of total perinatal deaths due to congenital malformation, with cardiovascular malformations accounting for 40% of the perinatal deaths .…”
Section: Introductionmentioning
confidence: 99%
“…In Africa, neonatal and perinatal deaths due to congenital abnormalities are much higher compared to Europe. In Tanzania, a high perinatal death of 66.7% and neonatal death of 18.5% are caused by congenital malformations . In Nigeria, an earlier study reported about 16% of total perinatal deaths due to congenital malformation, with cardiovascular malformations accounting for 40% of the perinatal deaths .…”
Section: Introductionmentioning
confidence: 99%
“…In Tanzania like most developing countries, limited estimates exist on the magnitude of folate deficiency[ 2 , 6 , 7 ]. As a proxy measure and sequel of folate deficiency among women of reproductive age, the birth prevalence of neural tube defects (NTDs) in Tanzania is estimated to be as high as 3 NTDs per 1000 live births[ 8 , 9 ]. It is estimated that micronutrient deficiencies cost Tanzania over US$ 518 million, estimated at 2.65% of the country’s GDP annually[ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neural tube defects(NTDs), which include spina bifida, anencephaly, craniorachischisis, and encephalocele, are among the most common human birth defects, with a worldwide prevalence of approximately 1 per 1000 births (Frey and Hauser, ). The prevalence of NTDs varies considerably by geographic areas, with prevalence reported as 0.2 to 14 per 1000 births (Busby et al, ; Li et al, ; Allagh et al, ; Kishimba et al, ). The etiology of NTDs is far from fully understood.…”
Section: Introductionmentioning
confidence: 99%